Low incidence of HIV infection in an anonymous HIV counselling and testing clinic cohort in Bangkok, Thailand despite high HIV prevalence and self-report of high-risk behaviour - Nittaya Phanuphak; Robert Paris; Donn Colby; Suteeraporn Pinyakorn; Mark Souza, de; Nipat Teeratakulpisarn; Nitiya Chomchey; Duanghathai Sutthichom; Amornrat Sukjitpaiboonphol; Tippawan Pankam; Jerome H. Kim; Jintanat Ananworanich; et al. (Elsevier, 2015)
Background: HIV counselling and testing (HCT) clinics have the potential to be entry points for recruiting populations at high risk for HIV infection for HIV prevention and treatment studies. Cohort data from key populations are crucial for HIV study site selection. Method: This cohort study recruited clients at an HCT clinic in Bangkok, Thailand. HIV prevalence was assessed along with demographics, perception of risk and behavioural risk factors. Participants who were HIV negative at baseline were followed up every 4 months for up to 1 year to measure HIV incidence and changes in risk behaviour. Results: A total of 992 subjects enrolled; median age was 30 years, 27% were men who have sex with men (MSM) and 8% were commercial sex workers (CSW). Baseline HIV prevalence was 10%. Factors positively associated with HIV infection were age >30 years, lower educational status and being MSM. Factors negatively associated with HIV infection were self-perception of minimal or moderate risk. Overall dropout rate was 49%, with 24% not returning after enrolment. HIV incidence was lower than expected at 0.50 per 100 person-years overall and 1.95 per 100 person-years for MSM. Conclusions: This HCT population had a high baseline HIV prevalence but a low incidence rate on follow-up. Overall retention in the cohort was poor and may have resulted from suboptimal reminders and characteristics of high-risk clients who use anonymous HIV testing services. MSM had higher HIV incidence and better retention than other high-risk groups.